Christian Spiritual Formation on the Digital Campus: A Theological Literature Review of E-Learning and Hybrid Learning - Budieli Hia; Andar Gunawan Pasaribu; Elisamark Sitopu; Lasmaria Lumban Tobing (Socio-Economic and Humanistic Aspects for Township and Industry, 2025)
This article presents a theological review of Christian spiritual formation on digital campuses shaped by e-learning and hybrid learning. Digitalization has expanded access and efficiency in higher education, but it also risks dehumanizing relationships, eroding silence, and reducing spirituality to formal online routines. The aim of this review is to clarify these risks and to propose a constructive framework for digital spirituality in Christian higher education, with particular attention to the Indonesian context. Using theological literature review combined with phenomenological reflection on recent empirical studies, the article first conceptualizes Christian spirituality in higher education as an integrated way of life grounded in the Triune God, encompassing relational love, intellectual discipleship, moral responsibility, and pastoral care. It then identifies three core challenges of the digital campus: weakened interpersonal presence, hurry-driven spiritual fatigue, and disembodied, ritualistic religiosity. In response, the article develops four key practices: incarnational spirituality in virtual spaces, digital spiritual disciplines, virtual faith communities, and online pastoral accompaniment. Finally, it articulates three institutional roles for the Christian digital campus: a prophetic role that critiques unjust and manipulative uses of technology, a pastoral role that nurtures a healing community for digitally burdened students, and a transformational role that integrates theology, ethics, and technology in curriculum and campus culture. The review concludes that digital campuses can become genuinely formative environments when technology is intentionally ordered toward worship, community, and mission under the lordship of Christ.